2012
DOI: 10.1021/bm301567w
|View full text |Cite
|
Sign up to set email alerts
|

A Chemically Functionalized Magnetic Nanoplatform for Rapid and Specific Biomolecular Recognition and Separation

Abstract: We have developed a target-molecule-functionalized magnetic nanoparticle (MNP)-based method to facilitate the study of biomolecular recognition and separation. The superparamagnetic property of MNPs allows the corresponding biomolecules to be rapidly separated from crude biofluids with a significant improvement in recovery yield and specificity. Various MNPs functionalized with tag molecules (chitin, heparin, and amylose) were synthesized for recombinant protein purification, and several probe-functionalized M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
(55 reference statements)
0
19
0
Order By: Relevance
“…Pioneering work of El-Boubbou et al [66] and Hatch et al [67] demonstrated that MNPs functionalized with glycoconjugates could be used to isolate and quantify Escherichia coli, reaching higher sensitivity and selectivity than the same MNPs functionalized with antibodies [67]. Since then, some other examples where glycoMNPs are used to detect bacteria can be found in the literature [68]. Parera Pera et al [48] exploited this concept for the detection, for the first time, of a gram-positive pathogen, Streptococcus suis.…”
Section: Pathogen and Cell Isolationmentioning
confidence: 99%
“…Pioneering work of El-Boubbou et al [66] and Hatch et al [67] demonstrated that MNPs functionalized with glycoconjugates could be used to isolate and quantify Escherichia coli, reaching higher sensitivity and selectivity than the same MNPs functionalized with antibodies [67]. Since then, some other examples where glycoMNPs are used to detect bacteria can be found in the literature [68]. Parera Pera et al [48] exploited this concept for the detection, for the first time, of a gram-positive pathogen, Streptococcus suis.…”
Section: Pathogen and Cell Isolationmentioning
confidence: 99%
“…Magnetic nanoparticles (NPs) have gained considerable attention in the past two decades. The outburst of research in this area is motivated by their broad technological applications including single‐bit elements in high‐density magnetic data storage arrays, contrast enhancement agents for magnetic resonance imaging (MRI), selective probes for biomolecular interactions, cell sorters, drug delivery, hyperthermia, etc. A promising application of magnetic NPs is as drug carriers for so‐called magnetic drug delivery .…”
Section: Introductionmentioning
confidence: 99%
“…Nanomedicine has become one of the choices for developing new drugs/ therapies. Nanomaterials coated with Gb 3 analogues have been successfully used to effectively target SLT-1B [26][27][28][29]. The beauty of using Gb 3 immobilized nanoparticles (Gb 3 -NPs) instead of Gb 3 analogues alone is that multivalent interactions are involved in the binding between Gb 3 -NPs with SLT-1B, leading to high binding affinity.…”
Section: Introductionmentioning
confidence: 99%